Descendance différentielles, reproduction générationnelle et enfants-utiles dans une population de type « isolée » de la montagne alpine (XVIe-XIXe siècles) - Gilles Boëtsch; Michel Prost (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
By mean of population database register, we study the progeny on 7 generations of individuals and couples in a French Alps valley from the XVIth to the XIXth century. In this highlander zone, according to different parameters, we observed a high reproductive behaviour diversity. The inhabitants of the valley of Vallouise are geographically and genetically isolated and the use of genealogical method shows very well the complexity of the domestic reproduction. Thus, well that in isolated situation, where practically every demographic events take place in the same place, we can try to understand the influence of a lot of parameters as the residence, the matrimonial structures or social classes that we can meet in the mountain area.